From one birth to the next: how cesarean section affects maternal physical activity and health in later pregnancy—A prospective cohort study - Szablewska, Anna Weronika; Zając, Bartosz; Santos-Rocha, Rita (Frontiers in Public Health, 2025)
BackgroundCesarean section (CS) is a common surgical procedure in obstetrics, and its prevalence has been increasing globally. While the immediate outcomes of CS are well-documented, its long-term effects, particularly on maternal health, remain an area of active research. One of the critical concerns is the impact of a previous CS on gestational body mass gain (GBMG), physical activity (PA) and the likelihood of undergoing another CS in subsequent pregnancies.ObjectiveThe aim of this study is to evaluate the potential association of a previous CS on GBMG, PA levels and the likelihood of repeat cesarean delivery in a cohort of multiparous women.MethodsThis prospective cohort study, enrolling 109 Caucasian women, was conducted at a tertiary care hospital in northern Poland. Participants were recruited from antenatal outpatient clinics. The participants were divided into two groups: those who underwent previous CS and those who had vaginal delivery. Data collection was conducted in two phases. In the first phase, socio-demographic information was gathered, and participants were asked to complete the Polish version of the Get Active Questionnaire for Pregnancy. In the second phase, biomedical data routinely collected during childbirth were obtained.ResultsWomen with a history of CS were found to have a significantly higher likelihood of excessive gestational GBMG and were more likely to undergo another cesarean delivery in subsequent pregnancies. However, no significant differences were observed between groups in terms of insufficient GBMG or PA levels before and during pregnancy.ConclusionsThe results allow to suggest that previous CS is associated with an increased risk of excessive GBMG and repeat cesarean delivery. However, it does not appear to have direct impact on PA levels during pregnancy. These findings emphasize the importance of monitoring GBMG and promoting healthy lifestyle behaviors to improve maternal and outcomes, particularly in women with a history of CS. Future research is needed to explore the long-term effects of CS on maternal health and its influence on subsequent pregnancies.